Antiproliferative metabolites from the Northern African endemic plant Daucus virgatus (Apiaceae). (November 2017) - Snene, Alì; Sirignano, Carmina; Rigano, Daniela; Formisano, Carmen; El Mokni, Ridha; Ercolano, Giuseppe; Dhaouadi, Hatem; Ianaro, Angela; Hammami, Saoussen; Taglialatela-Scafati, Orazio
Abstract: Chemical analysis of the dichloromethane fraction obtained from aerial parts of the Northern African endemic plant Daucus virgatus led to the isolation of three previously undescribed sesquiterpenoids, namely the daucane vaginatin B, a eudesmane and the elemane elemavirgolide, along with five known metabolites. The structures of these compounds were determined by a detailed MS and NMR analysis and they were evaluated for antiproliferative activity against three human cell lines, A375 (melanoma), MCF-7 (breast adenocarcinoma), and HACAT (keratinocyte). The phytoalexin 6-methoxymellein revealed a previously unreported antiproliferative activity, while the eudesmane and the elemane derivatives exhibited a selective activity (SI = 11.1 and 3.3, respectively) against melanoma tumor cell lines. Graphical abstract: Three previously undescribed angeloylated sesquiterpenes were isolated from Daucus virgatus along with five known compounds. The eudesmane and the elemane derivatives exhibited a selective activity against melanoma tumor cell lines.Image 1 Highlights: The first phytochemical analysis of the Tunisian plant Daucus virgatus is reported. Three previously undescribed angeloylated sesquiterpenoids have been characterized. Metabolites have been tested for antiproliferative activity against human cells. 6-Methoxymellein revealed a previously unreported antiproliferative activity. The eudesmane derivative exhibited a selective activity against melanoma cell lines.